2021
DOI: 10.1055/s-0041-1722875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of PCSK9 E670G and R46L Polymorphisms on Major Adverse Cardio-Cerebrovascular Events in Patients with ST-Segment Elevation Myocardial Infarction Undergoing Primary Percutaneous Coronary Intervention

Abstract: Major adverse cardio-cerebrovascular events (MACCE) in ST-segment elevation myocardial infarction (STEMI) are still high, although there have been advances in pharmacology and interventional procedures. Proprotein convertase subtilisin/Kexin type 9 (PCSK9) is a serine protease regulating lipid metabolism associated with inflammation in acute coronary syndrome. The MACCE is possibly related to polymorphisms in PCSK9. A prospective cohort observational study was designed to confirm the association between polymo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
(33 reference statements)
0
3
0
Order By: Relevance
“…PCSK9 is also detected in atherosclerotic plaques, contributing to the development and progression of atherosclerosis and thrombosis through a process involving platelet activation, leukocyte recruitment, as well as clot formation, and so on [ 17 ]. PCSK9 has been reported to regulate inflammation-related lipid metabolism in ACS, and its polymorphisms may be related to MACE [ 18 ]. PCSK9 is expressed in various cell types involved in the development and progression of atherosclerosis and can be detected in human atherosclerotic plaques [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…PCSK9 is also detected in atherosclerotic plaques, contributing to the development and progression of atherosclerosis and thrombosis through a process involving platelet activation, leukocyte recruitment, as well as clot formation, and so on [ 17 ]. PCSK9 has been reported to regulate inflammation-related lipid metabolism in ACS, and its polymorphisms may be related to MACE [ 18 ]. PCSK9 is expressed in various cell types involved in the development and progression of atherosclerosis and can be detected in human atherosclerotic plaques [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, PCSK9 levels greater than 310 ng/mL were associated with more severe coronary artery stenosis and a higher incidence of MACCE at follow-up. 30 The difference in traditional atherosclerosis risk factors in different Gensini score subgroups was not statistically significant in this study, possibly because the selected patients were older adults. Theocharidou et al reported that PCSK9 was associated with higher morbidity, mortality, and risk of major clinical adverse events in patients with NAFLD.…”
mentioning
confidence: 53%
“…6 Proprotein convertase subtilisin/kexin type 9 (PCSK9) refers to a serine protease-modulating lipid metabolism associated with inflammation in acute coronary syndrome. 7 Discovered in 2003, PCSK9 subsequently emerges as an innovative target for low-density lipoprotein cholesterol (LDL-C)lowering treatment. 8 PCSK9 performs a crucial role in myocardial infarction 9 and in the regulation of lipid metabolism.…”
mentioning
confidence: 99%